DOES MONETARY UNION DIFFUSE? THE FAILURE OF THE ECOWAS MONETARY UNION PLAN - Farhan Abdul Majiid (Universitas Jenderal Ahmad Yani, 2024)
In 2000, the Economic Community of West African States (ECOWAS) proposed the idea of a single currency. To this day, however, this plan remains unsuccessful despite several attempts being made to proceed with this ambition. This article will examine this failure from the perspective of regional diffusion theory, which suggests that one regional institution’s success will push others to follow its path. In examining this problem, this research uses primary literature from official documents of ECOWAS and secondary literature from related academic journals. The result of this research is that the soft persuasion explanation of regional diffusion is insufficient to replicate regionalism in other regional institutions. Thus, this paper argues that external actors’ hard prevention also contributes to diffusion failure using the ECOWAS case. e using the ECOWAS case.